2006
DOI: 10.1016/j.pmpp.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a cinnamyl alcohol dehydrogenase of Quercus suber in the defence response to infection by Phytophthora cinnamomi

Abstract: A gene encoding a potential NADPH-dependent cinnamyl alcohol dehydrogenase (QsCAD1) (GenBank accession no: AY362455) was identified in Quercus suber (cork oak). Its complete cDNA sequence was obtained by RACE-PCR, starting from total RNA extracted from roots of seedlings of Q. suber, infected with Phytophthora cinnamomi, the causal agent of the decline and sudden death of Q. suber and Quercus ilex subsp. rotundifolia in the Iberian Peninsula. Sequence information to perform the RACE-PCR was acquired from a pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…For a tolerant interaction, it is proposed that effector molecules like aldehyde aromatic compounds, similar to the eutypine toxin, released by P. cinnamomi during early infection, can be reduced and inactivated to alcohols by a Q. suber cinnamyl alcohol dehydrogenase 1 (QsCAD1) (Coelho et al. ). In the case of the sudden death phenotype, trees might contain inactive QsCAD1 proteins, as a result of polymorphic forms of the coding gene.…”
Section: Physiological Biochemical and Molecular Reactions Of Infectmentioning
confidence: 99%
“…For a tolerant interaction, it is proposed that effector molecules like aldehyde aromatic compounds, similar to the eutypine toxin, released by P. cinnamomi during early infection, can be reduced and inactivated to alcohols by a Q. suber cinnamyl alcohol dehydrogenase 1 (QsCAD1) (Coelho et al. ). In the case of the sudden death phenotype, trees might contain inactive QsCAD1 proteins, as a result of polymorphic forms of the coding gene.…”
Section: Physiological Biochemical and Molecular Reactions Of Infectmentioning
confidence: 99%
“…It was out of the scope of this work to ascertain lignin and phenol contents. However, cinnamyl alcohol dehydrogenase (CAD) genes have been shown to be up-regulated in Q. suber root seedlings infected with P. cinnamomi (Coelho et al 2006;Ebadzad and Cravador 2014) suggesting that the observed POD activity increase is related with the participation of this enzyme in the oxidation of the CADs.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called defence lignin (Hawkins and Boudet 2003) protects healthy tissue from water losses and infections. Increased CAD-enzyme activities or transcript levels upon elicitation by fungal pathogens, wounding, or ozone have been observed, for example, by Grand et al (1987), Galliano et al (1993), Mitchell et al (1994, and Coelho et al (2006). Valentines et al (2005) observed a very good correlation between lignin content and Penicillium expansum-resistance in apple and Nafussi et al (2001) between lignification and P. digitatum-resistance in citrus.…”
Section: Discussionmentioning
confidence: 99%